Site investigation and the law - Cottington, Jack (Thomas Telford, 1984)
A guide to the ICE Conditions of Contract for Ground Investigation, this title includes advice upon their interpretation and use and sets them in the context of a clear understanding of the law and the practice of ground investigation.